The Influence of Previous Biology Lessons on Prospective Teachers’ Beliefs About Learning Biology - Schumacher, Fabian; Basten, Melanie; Großschedl, Jörg; Klatthaar, Moritz; Wilde, Matthias (Frontiers in Education, 2021)
As a Professional teaching competence is significantly influenced by beliefs about learning. Prospective teachers start their teacher training at university with quite persistent beliefs about learning processes. Beliefs about learning can be differentiated into two perspectives: beliefs about student learning and beliefs about one’s own learning. Theoretical considerations suggest that the latter influence beliefs about student learning and both perspectives are influenced by the way in which prospective teachers experienced their own lessons as pupils at school. We investigated how prospective biology teachers remembered their own biology lessons and how these experiences influenced their beliefs about learning regarding both perspectives. The sample consisted of 164 prospective biology teachers (M(age) = 21.58 years, SD(age) = 2.5, 66.02 % female) in Germany. Results of a simple mediation model indicate that previous experiences in biology lessons had an impact on both perspectives. Moreover, we found that the influence that previous lessons had on the beliefs about student learning was fully mediated by one’s beliefs about own learning processes. This suggests that experiences from one’s own schooling have an impact on how teachers view learning of their students. As implications for teacher training and future research, our findings suggest that both perspectives of beliefs need to be further taken into account and that an explicit focus on beliefs about teachers’ own learning is needed.